Modelagem da via de regulação gênica de ácidos graxos da bactéria Escherichia coli K12 utilizando redes booleanas - SANTOS, Wendel Renan Macedo dos (2020)
Systems Biology is the science that describes the behavior of a system through mathematical and computational modeling. It is a multidisciplinary and recent area in bioinformatics. Using a holistic approach, it seeks to understand the biological complexity of living things. On a biological level, we can represent our organism as a set of integrated metabolic networks that form the whole. Systems biology studies these metabolic networks to understand the behavior of the organism and to propose hypotheses, computational models and contribute to the study of biological functions. In this work, the regulation network of the gene expression of fatty acids of the model organism Escherichia coli k12 is studied. Gene expression regulation is a mechanism of cellular control that ensures that genes in an organism are expressed according to need, governing the individual's ability to respond to stimuli and adapt to the environment. We can simplify this process by stating that the regulation of gene expression controls the activation or repression of genes. From this principle, a similarity was detected between the process of gene regulation and a computational modeling technique called Boolean Networks. These networks work with binary values 0 and 1. In Boolean modeling we use the basic operations AND, OR and NOT to represent the transitions that occur in the biological model. These grouped operations form Boolean networks. In this work we use this principle to model the metabolic pathway of the model organism, based on information contained in the genome available in biological databases. The results obtained show the relationships between the genes of the fatty acid pathway according to the KEGG database in the form of Boolean networks.